Local and systemic recurrence patterns of urothelial cancer after radical cystectomy - Sait Özbir; Cengiz Girgin; Cengiz Kara; Çetin Dinçel (Kaohsiung Journal of Medical Sciences, 2014)
The aim of this study was to evaluate the local recurrence and distant metastasis rates for urothelial carcinoma of the bladder after radical cystectomy and to identify the predictive factors for local recurrence and distant metastasis. The study population was 347 consecutive patients treated with radical cystectomy for urothelial carcinoma of the bladder at our institution. Local recurrence, distant metastasis, and both local and distant recurrence rates were 49 (14.1%) months, 96 (27.7%) months, and 17 (4.9%) months, respectively. The mean follow-up times to recurrence were 14.37 ± 13.25 months (range, 2–60 months) and 14.43 ± 15.72 months (range, 2–109 months) for local recurrence and distant metastasis, respectively (p = 0.808). The mean post-recurrence disease-specific survival (PRDSS) times for local, distant, and both local and distant recurrences were 17.82 ± 3.18 months, 4.16 ± 0.39 months, and 11.41 ± 2.73 months, respectively (p < 0.001). The predictive factors for local recurrence and distant metastasis were stage and nodal involvement (p < 0.001). Sex, grade, lymphovascular invasion (LVI), carcinoma in situ (CIS), and lymph node density (LND; 10% cut-off value) were not predictors for recurrence in the results of the multivariate analysis. The current study demonstrated that stage and pathological nodal involvement were independent predictors of local recurrence and distant metastasis. The results of this study suggest that the early diagnosis and intervention of invasive bladder cancer cases may decrease the number of high stage and lymph node positive cases that have a high risk of local and distant recurrences. The adjuvant treatment options in the presence of risk factors for recurrence may improve survival outcomes.